Impact of sales staff turnover on customer equity in the South African luxury automotive industry - Mbonwa, Sthandweyinkosi Ntokozo (My University, 2016)
The purpose of this study was to understand the impact of sales staff turnover on customer equity in the South African luxury automotive industry. The concept customer equity has three elements that load onto it, namely; value equity, brand equity and relationship equity. For the purpose of this study, the focus was on relationship equity as this is the one customer equity element that the Sales Executives are able to influence. Rust, Zeithaml, and Lemon (2001) are of the view that customer equity drivers vary in importance for different industries. In relationship orientated industries (e.g. banking and automotive industry), relationship equity may be the most important driver of customer equity. Relationship equity is also known as retention equity as it entails the customers conscious decision to stick with a certain brand even after having conducted thorough research and analysis of other brands (Lemon, Rust, & Zeithaml, 2001). The study used a quantitative research method and the data is founded on the results from 73 surveys received from customers who own luxury vehicles, namely Audi. The data was analysed utilising multiple regressions, using the independent t-test to accept or reject the proposed hypotheses. Understanding the impact of sales staff turnover on relationship equity in the automotive sector is critical as this industry currently suffers from very high Sales Executive turnover. Original Equipment Manufacturers and dealer management need to understand the impact of this high staff turnover on the customers and ultimately potential future sales so that they may be able to mobilise effective strategies to minimise any negative impact caused by sales staff churn. The theoretical framework for this study is taken from a model by Vogel, Evanschitzky, and Ramaseshan (2008), which looks at the 3 drivers of customer equity and how these drivers effect customer loyalty intentions and future sales. This study found that sales staff turnover has a strong, significant relationship to relationship equity, meaning that sales staff turnover negatively affects relationship equity for the organisation, and therefore negatively affects the customer experience.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing Johannesburg, 31 March 2016
Keywords: Consumer behavior--South Africa; Customer relations--South Africa; Labor turnover--South Africa; Motor vehicle industry--South Africa